PENERAPAN METODE BLOCK CIPHER GOVERNMENT PADA APLIKASI PEMBELAJARAN KRIPTOGRAFI - Kurnia Yahya (P3M STMIK Profesional Makassar, 2018)
Cryptography is also known in the world of education, especially the field of information technology. Some lecture places are often found learning about cryptography that only deals with theories without directly seeing what is happening in the cryptographic process, so that in this final project will be made a cryptographic algorithm learning application that can simplify in learning some process that happened in cryptografi especially the standard block cipher government method. The process that occurs for the first time in this method is the process of forming keys, encryption and decryption processes that have certain functions such as substitution box, rotate left shift, XOR operation and modulo operations are elaborated with more detailed visualization and gradual data changes.